Altered taste perception in oral submucous fibrosis: A research - R Deeplaxmi; Subhash B Sakarde; Jaideep Sur; Anand Pratap Singh; Supreet Jain; Sheetal Mujoo (Wolters Kluwer Medknow Publications, 2012)
The sense of taste is among the regulatory mechanism for acceptance or rejection of foods. In oral submucous fibrosis (OSMF) patients, impairment of taste sensation has not received much attention, owing to limited research work in the field. This study was conducted to analyze the taste impairment in OSMF patients by using four basic tastes: Sweet, sour, salty and bitter, among a group of 30 subjects by using physiological taste stimuli tastants. In OSMF, significant taste alteration was found with sweet followed by salt, bitter and sour.